Competition and Hospital Quality: Evidence from a French Natural Experiment - Laurent Gobillon; Carine Milcent (Institute of Labor Economics (IZA), 2017)
We evaluate the effect of a pro-competition reform gradually introduced in France over the 2004-2008 period on hospital quality measured with the mortality of heart-attack patients. Our analysis distinguishes between hospitals depending on their status: public (university or non-teaching), non-profit or for-profit. These hospitals differ in their degree of managerial and financial autonomy as well as their reimbursement systems and incentives for competition before the reform, but they are all under a DRG-based payment system after the reform. For each hospital status, we assess the benefits of local competition in terms of decrease in mortality after the reform. We estimate a duration model for mortality stratified at the hospital level to take into account hospital unobserved heterogeneity and censorship in the duration of stays in a flexible way. Estimations are conducted using an exhaustive dataset at the patient level over the 1999-2011 period. We find that non-profit hospitals, which have managerial autonomy and no incentive for competition before the reform, enjoyed larger declines in mortality in places where there is greater competition than in less competitive markets.
Keywords: I11; I18; 330; competition; hospital ownership; policy evaluation; heart attack